Community Empowerment through the Family Development Session of the Family Hope Program (Case Study) - Purnomo, Eko; Trihatmoko, R. Agus; Martomo, Yitno Puguh (Journal of Management and Administration Provision, 2025)
Community empowerment is a strategic approach in overcoming complex poverty. This research aims to analyze the implementation, results, obstacles and solutions for community empowerment through Family Development Sessions (FDS) in the Family Hope Program (PKH) in Kadipiro Village, Sambirejo District, Sragen Regency. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, participant observation and documentation studies. Research informants were selected purposely, consisting of social assistants and Beneficiary Families (KPM). The research results show that FDS plays an important role in increasing KPM's awareness, abilities and life skills. However, there are obstacles such as low KPM participation, limited accompanying resources, and a lack of effective training modules. The proposed solutions include developing modules based on local needs, increasing companion training, and optimizing participatory strategies. This research provides important insights for the development of more inclusive and sustainable community empowerment programs.